Purify and Characterize the Xylanase from the Local Isolation of Trichoderma Longibrachiatum - Shimal Younis Abdel-Hadi (Journal of Global Pharma Technology, 2020)
Fungi are well known for their ability to produce extracellular enzymes into their surrounding environment. Xylanases are an important class of hydrolytic enzymes involved in degradation of xylene a backbone of hemicellulose, in this study; we have isolated three isolates of xylene analytic fungi taken from five samples of sand gathered from different sites in the University of Mosul. Depending on the halo's diameter of analysis and by using the Congo red indicator, one isolate has got a high activity in producing the exocellular xylanase enzyme related to Trichoderma longibrachiatum on the base of morphological, microscopic and internal area (ITS) features. The xylanase has been purified from the raw extracted enzyme of the selected isolate throughout four subsequent steps included: sedimentation by Ammonium Sulphate, dialysis, gel filtration in column (Sephadex-G 100) and the Ionic exchanger (DEAE Cellulose). After this step, the number of filtrations is (49.22) with enzymatic outcome reaching to (33.93%). Studying the description of the filtered enzyme, PH the optimal for the enzyme activity is 0.5 and the optimal range of PH for enzyme stability is (4-6). Moreover, the optimal temperature degree for enzyme activity is (50 °C), whereas the optimal temperature degree for enzyme stability is (50-60 °C).Keywords: Mosul university, Xylanase, Trichoderma longibrachiatum.